h - Liu, Zhiming; Woodcock, Jim.; Zhu, Huibiao; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 10th International Colloquium on Theoretical Aspects of Computing, ICTAC 2013 held in Macau, China, in September 2013. The 22 revised full papers presented together with three keynote talks were carefully reviewed and selected from 64 submissions. The papers cover various topics related to both theoretical aspects of computing and the exploitation of theory through methods and tools for system development.
Stochastic Pi-calculus Revisited -- A Clock-Based Framework for Construction of Hybrid Systems -- Advances in Quantitative Verification for Ubiquitous Computing -- Mobile Membranes: Computability and Complexity -- Cruise Control in Hybrid Event-B -- From Distributions to Probabilistic Reactive Programs -- Hol-TestGen/fw: An Environment for Specification-Based Firewall Conformance Testing -- Random Walks on Some Basic Classes of Digraphs -- A Probabilistic Logic for pTiMo -- An Interface Model of Software Components -- A High-Level Semantics for Program Execution under Total Store Order Memory -- Preemptive Type Checking in Dynamically Typed Languages -- On Refinements of Boolean and Parametric Modal Transition Systems -- Proof Theory of a Multi-Lane Spatial Logic -- Counterexample-Preserving Reduction for Symbolic Model Checking -- A Transformation from p-pi to MSVL -- On Slicing of Programs with Input Statements -- Deterministic Logics for UL -- Finitary Fairness in Action Systems -- Spatio-temporal Hybrid Automata for Cyber-Physical Systems -- Embedding Functions into Disjunctive Logic Programs -- Reactive Designs of Interrupts in Circus Time -- A Proof System in PADS -- Scope Logic: An Extension to Hoare Logic for Pointers and Recursive Data Structures -- Durative Graph Transformation Rules for Modelling Real-Time Reconfiguration.
Keywords: Computer science; Software engineering; Logic design; Artificial intelligence; Computer Science; Logics and Meanings of Programs; Software Engineering; Artificial Intelligence (incl. Robotics).